Kinematics, Singularity and Workspace Analysis of a Novel 3T Parallel Mechanism Based on SKC - Zhao Yi'nan; Shen Huiping; Lu Chenfang; Huang Xiaoping (Jixie chuandong)
According to the theory and method of topological design of the parallel mechanism (PM) based on position and orientation characteristic (POC) equations, a novel three-translation (3T) parallel mechanism for grasping is proposed. Firstly, the design process of the entire PM is described and the main topological features of the mechanism are analyzed. It is proved that the mechanism contains two sub-kinematics chains (SKCs） whose coupling degree equals 0. Secondly, according to the kinematics modeling principle for parallel mechanism based on topological features, the direct kinematics problem (DKP) and inverse kinematics problem (IKP) of the mechanism are solved according to the order of SKC. Then, according to the singularity analysis method based on SKC theory, the first and second kind of singular configurations in each SKC are analyzed. Finally, the task workspace with the optimal internal velocity transmission factors index of the mechanism is analyzed and selected. This study lays the foundation for the stiffness, dynamics and engineering prototype design of the mechanism.